1995
DOI: 10.1111/j.1460-9592.1995.tb00277.x
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide in the management of persistent pulmonary hypertension of the newborn—an unusual cause of failure

Abstract: A diagnosis of persistent pulmonary hypertension of the newborn should be reviewed if there is a failure to respond to appropriate treatment. We report a case in which both conventional therapy and inhaled nitric oxide failed to break the cycle of right-to-left shunting. Reassessment revealed a massive pulmonary arteriovenous malformation for which surgery was successfully performed in the neonatal period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Since then there have been six additional reports of neonatal PAVMs. 3,4,[6][7][8][9] As in this case, the most pronounced feature of neonatal presentations is cyanosis that is unresponsive to supplemental oxygen and mechanical ventilation. Other respiratory symptoms include tachypnea and respiratory distress.…”
Section: Discussionmentioning
confidence: 69%
“…Since then there have been six additional reports of neonatal PAVMs. 3,4,[6][7][8][9] As in this case, the most pronounced feature of neonatal presentations is cyanosis that is unresponsive to supplemental oxygen and mechanical ventilation. Other respiratory symptoms include tachypnea and respiratory distress.…”
Section: Discussionmentioning
confidence: 69%
“…They found spontaneous regression in the size of the feeder vessel as well as in the size of vascular bed of the congenital hepatic AVM with conservative use of oral heart failure therapy with diuretic agents and captopril observed a decrease in the congestion and diameter of the affected vessels. Although we do not have any pulmonary AVMs in our study population, Jerwood DC et al reported a case of pulmonary AVM in which right-to-left shunting still occurred regardless of the therapy used [13]. Upon reassessment a substantial pulmonary AVM was found, a surgery was performed during the neonatal period which turnout to be successful.…”
Section: Discussionmentioning
confidence: 75%
“…However, its use in infants with increased pulmonary blood ow (PBF) remains questionable as it can worsen the symptoms of congestive heart failure (CHF). Jerwood and Stokes reported a case of PH, where a massive pulmonary AVM was found to be the underlying cause of reassessment [13]. Hendson et al reported using iNO to decrease pulmonary pressures in the case of cerebral AVMs.…”
Section: Introductionmentioning
confidence: 99%
“…They observed a decrease in the congestion and diameter of the affected vessels. Although we do not have any pulmonary AVMs in our study population, Jerwood DC et al reported a case of pulmonary AVM in which right-to-left shunting still occurred regardless of the therapy used [ 13 ]. Upon reassessment, substantial pulmonary AVM was found, and surgery was performed during the neonatal period, which turned out to be successful.…”
Section: Discussionmentioning
confidence: 86%
“…However, its use in infants with increased pulmonary blood flow (PBF) remains questionable as it can worsen the symptoms of congestive heart failure (CHF). Jerwood and Stokes reported a case of PH, where a massive pulmonary AVM was found to be the underlying cause of reassessment [ 13 ]. Hendson et al reported using iNO to decrease pulmonary pressures in the case of cerebral AVMs.…”
Section: Introductionmentioning
confidence: 99%